Implicaciones de las Niif´S S1 Y S2 en las pymes comerciales ecuatorianas - Chiquito Cañar, Tatiana Paola (2025)
This study explores in depth the implications of the adoption of International Financial Reporting Standards (IFRS) S1 and S2 in Ecuadorian small and medium-sized commercial enterprises (SMEs). These standards, focused on sustainability and related financial reporting, seek to improve the quality of financial information, but their implementation poses both opportunities and challenges, through a mixed methodological approach, which combines documentary analysis on commercial SMEs according to their sales revenue in pre- and post-implementation IFRS financial information, The findings indicate that the adoption of IFRS has resulted in greater transparency and comparability of financial reporting, promoting an alignment with international standards that facilitates market access and investor confidence, However, the study also reveals that many SMEs face significant difficulties in the implementation process, especially in terms of the training required and the associated costs, which can put their financial sustainability at risk in the short term. Likewise, a lack of adequate technological infrastructure for effective compliance with these standards is detected, the conclusions underline the urgent need for greater institutional support and public policies that encourage the adoption of IFRS through specialised training programmes and access to technological tools, which would facilitate the transition and maximise the potential benefits of these regulations in the Ecuadorian context.